High Level Physical Activity and Prevalence of Cardiovascular Disease Using the Korea National Health and Nutrition Examination Survey Data, 2007-2013 - Kyounghoon Park; Byung-Joo Park (Korean Society for Preventive Medicine, 2017)
Objectives The purpose of our study was to evaluate the association between the intensity of physical activity (PA) and prevalence of cardiovascular disease (CVD) using Korean representative data. Methods We analyzed 39 804 participant data from the Korea National Health and Nutrition Examination Survey, 2007-2013. Exposure variable was three levels of PA (low, medium, and high) in a week, and outcome variable was prevalence of CVD based on patient self-recognition and doctor's diagnosis. Complex logistic regression analysis was performed to evaluate the relationship between level of PA and CVD adjusted by body mass index, hypertension, hypercholesterolemia, diabetes mellitus, stress recognition, household income, smoking, and current drinking. The indices of association w ere estimated as crude prevalence odds ratio (POR), adjusted POR, and their 95% confidence interval (CI). All statistical analyzes were performed using complex sample analysis procedure of the SPSS version 23.0. Results When all variables were adjusted, only high level PA in women showed a significant association with stroke (adjusted POR by patient's self-recognition, 0.57; 95% CI, 0.32 to 0.99, adjusted POR by doctor's diagnosis, 0.55; 95% CI, 0.34 to 0.87) and CVD (adjusted POR by doctor's diagnosis, 0.68; 95% CI, 0.48 to 0.96). Conclusions High level PA in women has a significant reverse association with prevalence of stroke and CVD in Korea. Further study for elucidating the mechanism will be needed.